Criticism, consensus, and fandom: Demonstrated practices from a sports Facebook fan page. (June 2019) - Avalos, Xima; Dori-Hacohen, Gonen
Highlights: Fandom and criticism are discussed in relation to a public. Criticism is a dilemma for sport-fans who admire a team. Fans use emoticon and irony to mitigate the dilemma. Consensus allows unabashed criticism and leads to action.